Polska prasa prawicowa wobec interwencji Włoch i III Rzeszy w Hiszpanii 1936–1939 - Opioła, Wojciech (Wydawnictwo Uniwersytetu Wrocławskiego, 2010)
The civil war in Spain which lasted from 1936 to 1939 soon transformed itself from a purely domestic conflict into a war involving – on both sides – over a dozen countries, including a lot of significant powers. Mussolini’s Fascist regime and Nazi Third Reich supported right-wing side of the conflict. Spanish war was widely commented in Polish right-wing press, both in Church papers which were connected with National Democracy and in those associated with less significant circles. The press of National Unity Camp after 1936 with respect to its views on Spanish civil war can also be placed in the same journalistic category. Publicists also remarked on the Fascist powers’ help for General Franco troops. Some of them were silent on this subject or belittled its importance by lessening the impact of Fascist aid while at the same time attacking Soviet Union for providing help for Republican side. Nevertheless the right-wing discourse was dominated by favorable opinions on this issue the emotional stance of which ranged from enthusiasm, through pragmatism, to critical acceptance as a choice of lesser evil. Polish political Right before World War II had a lot in common with Fascist and National Socialist ideology: it was branded with a stigma of Anti-Semitism which was quite strongly and fervently promulgated both by politicians and by the Church. Distinguishable echoes of militarism or imperialism and firm attachment to Catholic values were also present in the consciousness of journalists and society. These facts provide – at least to some degree – an explanation as to why Polish Right generally exhibited enthusiasm and approval for Spanish national rebels. A reception of Carlism also appears important in this context – this branch of political thought was notably popular among Polish Nationalist, Monarchist and Catholic circles in the first half of the twentieth century. For Polish Right Spanish civil war serving as a useful and helpful instrument of Anti-Communist propaganda which was carried on a very large scale. Fascism was often treated as a painful vaccination against Communist plague.
Keywords: prasa polska; prawicowa prasa; faszyzm; Włochy; III Rzesza; Hiszpania